2013
DOI: 10.2478/ama-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Air Flow Analysis for Electrical Motor's Cooling System With Autodesk Simulation CFD 2013 Program

Abstract: In the article the analysis of airflow through electrical motor was conducted and optimal design solution was chosen in order to increase cooling efficiency. Numerical simulations allow to determine the areas of temperature occurrence which may have destructive influence on electrical motor parts and on its safe operation. The numerical calculations of airflow was carried out for two different types of fans as well as for two different housings. An analysis of the construction was carried out by CFD method usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Based on the calculated safety factor, the chamber can withstand an external pressure of 202.6 kPa, which is twice the atmospheric pressure limit. The simulation result was consistent with the maximum allowable external pressure (199.6 kPa) that was calculated using the ASME simplified calculations for an external pressure vessel [19].…”
Section: Chamber Structural Integritysupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the calculated safety factor, the chamber can withstand an external pressure of 202.6 kPa, which is twice the atmospheric pressure limit. The simulation result was consistent with the maximum allowable external pressure (199.6 kPa) that was calculated using the ASME simplified calculations for an external pressure vessel [19].…”
Section: Chamber Structural Integritysupporting
confidence: 83%
“…A 400 mm space is created between the holes, which means that all the steam is concentrated at the wall of the chamber. Using Autodesk CFD 2024 [19], the steam path was simulated, the hole's locations were adjusted, and four additional holes were added to optimize the steam distribution inside the chamber. The existing holes of the hollow shaft were patched, and eight new holes with a diameter of 10 mm were drilled: four at the bottom and four at the top, with a 200 mm space between the centers of the holes (Figure 5).…”
Section: Modification Processmentioning
confidence: 99%
“…For this, it was necessary to simulate the flow under real conditions and to validate the performance of the waterwheel, using finite volume calculation by computer, which is used by CFD techniques [20]. The software used was Autodesk Simulation CF, which is also used in multiphase water-air research [21,22] and other areas [23,24].…”
Section: Cfd Simulationmentioning
confidence: 99%
“…The axial and radial fans were examined both experimentally and numerically to show that one of the axial fan designs improved motor efficiency while keeping the temperature constant [13]. The performance studies conducted on two separate fans to examine the cooling performance with Autodesk CFD 2013 software showed that the cooling with the axial fan was slightly lower than the radial fan [14]. The study on air gap between the stator and rotor in rotating electrical machines successfully verified the simulation outputs of six correlation equations given in the literature [15].…”
Section: Introductionmentioning
confidence: 99%